Vote of judges as an element constituting iudicium part. 1 - the concept of vote and and the relation to objective truth and moral certainty - POKORSKI, KRZYSZTOF (Prawo Kanoniczne, 2019)
During the canonical process, various documents are created, which are important for procedural activities. One of such documents is a judge's vote. It is the presentation of arguments that have their source in the course of the whole process and efforts that the judge undertook to discover the truth and achieve moral certainty. This wording of the vote is the fulfillment of the role of the judge in the canonical process and the implementation of the judicial authority of the church judge.